Kesehatan dan Lingkungan dalam Perspektif Sejarah: Perkembangan Baru Historiografi Indonesia - Emalia, Imas (Jurnal Sejarah Indonesia, 2023)
This article will explain the new developments in Indonesian history writing since entering the 2000s. The theme of health and the environment is increasingly in demand among academics, including historians. The 2019 coronavirus disease (covid) phenomenon that has hit most parts of the world brings various lessons to human life, including learning history. Among academics, researchers, historians, and students, writing on the theme of health and the environment continues to stretch as if it is a new trend. This period can be said to be the period of 'performance' of health and environmental research. Both of these themes have become prima donna in various campus events, health institutions, and places of worship. Until now, the two themes are still in demand by history students. Unfortunately, the guidelines or framework of reference (Learning Program Units/SAP) do not yet exist, so it seems there is "a void" in the historical and historiographical methodology space. Even though the findings of historical data have told a lot about past community events related to health and the environment, starting from epidemics, policies, institutions, and environmental damage, to wastewater treatment. Therefore, the purpose of writing this article is to contribute to thinking about the development of the theme of historical writing, so that new themes by the trends of the times can be written from a historical perspective. The research problem raised is how health and the environment are written from a historical perspective. The writing of this article uses the historical method with a social history approach.